2016
DOI: 10.1128/iai.01203-15
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NADH Oxidase in Competition and Endocarditis Virulence in Streptococcus sanguinis

Abstract: c Here, we report for the first time that the Streptococcus sanguinis nox gene encoding NADH oxidase is involved in both competition with Streptococcus mutans and virulence for infective endocarditis. An S. sanguinis nox mutant was found to fail to inhibit the growth of Streptococcus mutans under microaerobic conditions. In the presence of oxygen, the recombinant Nox protein of S. sanguinis could reduce oxygen to water and oxidize NADH to NAD ؉ . The oxidation of NADH to NAD ؉ was diminished in the nox mutant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…NADH oxidase contributes to the pathogenesis of S. pneumoniae, Group B Streptococcus and Streptococcus sanguinis. 12,13,15,29 In this study, we demonstrated that the virulence of S. suis 2 in a murine infection model was completely abolished by deletion of nox. The survival rates were significantly higher in mice infected with the Dnox mutant than in those infected with the WT and CDnox strains.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…NADH oxidase contributes to the pathogenesis of S. pneumoniae, Group B Streptococcus and Streptococcus sanguinis. 12,13,15,29 In this study, we demonstrated that the virulence of S. suis 2 in a murine infection model was completely abolished by deletion of nox. The survival rates were significantly higher in mice infected with the Dnox mutant than in those infected with the WT and CDnox strains.…”
Section: Discussionmentioning
confidence: 57%
“…This is not surprising, as S. suis NADH oxidase shows considerable identity to its orthologs from various streptococcal species, which have been shown to be involved in oxidative stress response and virulence. [12][13][14][15]29 The Dnox mutant exhibits reduced resistance to oxidative stress generated by environmental oxygen and hydrogen peroxide. This result is in agreement with the observed effects of spxA1 deletion in S. suis and nox2 deletion in Group B Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in the genes encoding lipoprotein SsaB (a putative manganese transport protein) (38), spxA1 (encoding a global regulator involved in H2O2 production) (138) and nox (encoding an NADH oxidase that also influences H2O2 production) (139), together with the anaerobic ribonucleotide reductase already mentioned, have all been shown to impair the capacity of S. sanguinis to cause IE. This suggests that the ability of S. sanguinis to adapt to differences in oxygen tension and the production of and resistance to reactive oxygen species are important in the development of IE, although molecular details have yet to be explained.…”
Section: S Sanguinis As An Etiological Agent Of Extraoral Diseasesmentioning
confidence: 99%